Effects of house type and early feed restriction on performance and fat deposition in unsexed broilers - Santoso, U (Indonesian Animal Sciences Society, 2002)
The present experiment was conducted to evaluate the effects of house type and early feed restriction on performance and fat deposition of unsexed broilers. Four hundreds seven-day old unsexed broilers (Arbor Acres CP 707) were distributed into eight treatment groups. Each treatment group was represented by five replicates of ten broilers each. Two types of house (cage vs litter) and four levels of feeding (ad lib., 75% ad lib., 50% ad lib. and 25% ad lib.) were tested as treatment factors. Broilers were feed-restricted for 6 days from 7 to 13 days of age and thereafter they were fed ad lib. Feed intake of restricted broilers during restriction period was calculated from feed consumed by ad lib. group in the previous day. Results showed that unsexed broilers raised in litter had higher body weight (P<0.05), lower abdominal fat and higher triglyceride concentration at 42 days of age (P<0.05), and lower liver fat and higher carcass percentage at 56 days of age (P<0.05). Early feed restriction reduced body weight of 42-day old unsexed broilers except for broilers fed 75% ad lib. At 56 days of age, restricted broilers had similar body weight to those fed ad lib. At 56 days of age, broilers fed 25% ad lib. had lower FCR (P<0.05), lower abdominal fat (P<0.05) and lower triglyceride concentration (P<0,05). In conclusion, unsexed broilers fed 25% ad lib. showed compensatory growth with better FCR and lower fat accumulation at 56 days of age. Broilers raised in litter had higher body weight and lower abdominal and liver fat deposition. Â Key words: House type, early feed restriction, fat deposition, unsexed broilers